Makna Relasi Gender dalam Islam dan Tao (Tinjauan Kritis dalam Pemikiran Etin Anwar dan Sachiko Murata) - Azizah, Azhar; Nadroh, Siti (Inklusiva: Jurnal Studi Agama-Agama, 2023)
Islam and Tao actually emphasize the formation of harmonious gender relations. The concept of harmony in Islam through Etin Anwar’s critical thinking is based on the principles of spiritual equality and ethical equality, while the Taoist concept of harmony through Sachiko Murata’s critical thinking is based on Taoist cosmology. If Islam based on the concept of Tauhid and the ethical message of Qur’an which are united of inclusive humanity through the principle of a harmonious sakinah-mawaddah-warahmah family to achieve the principle of Rahmatan Lil ‘Alamin. On the other side, Tao is based on the concept of Tao and Love as a harmonious unity which produces the yin-yang principle in building complementary relationships and balance. Analysis in interpreting gender relations in Islam and Taoism ultimately resulted in the formulation of the existence of ‘pair relationships.’